Enhanced oxidative stress is associated with tissue neutrophilia and poor steroid response in chronic rhinosinusitis with nasal polyps - Xian‐Ting Hu; Bai‐Wen Chen; Yu‐Jie Cao; Chun Zhou; Hua‐Bin Li; De‐Hui Wang (World Journal of Otorhinolaryngology-Head and Neck Surgery, 2023)
Abstract Objective To analyze the oxidative stress status and its association with tissue neutrophilia and oral steroid response in chronic rhinosinusitis with nasal polyps (CRSwNP) patients. Methods The levels of total oxidant status (TOS) were detected in the sinonasal tissues by using specific assay kits. Tissue neutrophil was examined by immunohistochemical staining, and oxidant status index (OSI) was evaluated in polyps tissues, and the messenger RNA (mRNA) levels of superoxide dismutase 2 (SOD2), aldehyde dehydrogenase 1 (ALDH1A1), and microsomal glutathione S‐transferase 1 (MGST1) were examined using quantitative real‐time polymerase chain reaction in the sinonasal tissues. The receiver operating characteristics (ROCs) curve of ALDH1A1, MGST1, and SOD2 mRNA levels were evaluated to determine the steroid response of CRSwNP patients. Results The levels of TOS and OSI were significantly higher in CRSwNP and CRSsNP than in normal controls, and OSI in polyps tissues was positively associated with tissue neutrophilia and poor steroid response. The ALDH1A1, MGST1, and SOD2 mRNA levels showed comparable accuracy as predictors of poor steroid response indicated by the area under the curve. Conclusion These findings provided evidence that the increased level of oxidative stress contributes to enhanced tissue neutrophilia and poor steroid response in CRSwNP patients.